2007
DOI: 10.1002/bip.20693
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an extruded nucleotide on cleavage activity and dynamic catalytic core conformation of the hepatitis delta virus ribozyme

Abstract: The self-cleaving hepatitis delta virus (HDV) ribozyme is essential for the replication of HDV, a liver disease causing pathogen in humans. The catalytically critical nucleotide C75 of the ribozyme is buttressed by a trefoil turn pivoting around an extruded G76. In all available crystal structures, the conformation of G76 is restricted by stacking with G76 of a neighboring molecule. To test whether this crystal contact introduces a structural perturbation into the catalytic core, we have analyzed approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 47 publications
(100 reference statements)
0
19
0
Order By: Relevance
“…A cis-acting precursor model exhibits greater fluctuations in fitness, whereas multimodal stacking of a U-1G mutation with U23 results in decreased fitness A wealth of experimental evidence has indicated that cisacting HDV ribozymes generally cleave ∼10-100 times faster than their trans-acting counterparts Shih and Been 2002;Sefcikova et al 2007a;Tinsley and Walter 2007;Chen et al 2009). It has been hypothesized that the loss in catalytic activity of trans-acting ribozymes is due to a less poised or stable cleavage site architecture as a result of the distal discontinuity of the RNA backbone (Shih and Been 2002;Tinsley and Walter 2007).…”
Section: Intermolecular Crystal Contacts Andmentioning
confidence: 99%
“…A cis-acting precursor model exhibits greater fluctuations in fitness, whereas multimodal stacking of a U-1G mutation with U23 results in decreased fitness A wealth of experimental evidence has indicated that cisacting HDV ribozymes generally cleave ∼10-100 times faster than their trans-acting counterparts Shih and Been 2002;Sefcikova et al 2007a;Tinsley and Walter 2007;Chen et al 2009). It has been hypothesized that the loss in catalytic activity of trans-acting ribozymes is due to a less poised or stable cleavage site architecture as a result of the distal discontinuity of the RNA backbone (Shih and Been 2002;Tinsley and Walter 2007).…”
Section: Intermolecular Crystal Contacts Andmentioning
confidence: 99%
“…A simplified analysis of only a few heteroatom distances of interest accompanied by generally uninformative root-mean-square distance (rmsd) plots may mask considerable problems. The structural evolution results from a mixture of factors, including the actual stochastic flexibility of the RNA, experimental artifacts introduced through crystal contacts,(8) disorder or chemical modification, and force field artifacts. If this mixture is properly resolved the analysis of MD simulations can be very insightful.…”
Section: What Practical Considerations Arise During Implementation Ofmentioning
confidence: 99%
“…(53) Multiple simulations reveal the rapid loss of this particular conformation and suggest a possible role of G76 in promoting catalysis through novel hydrogen-bonding interactions with stem P1. (8) Similarly, inactivating 2′-deoxy or 2′-O-methyl backbone modifications or base mutations used to trap ribozymes in their precatalytic structures may distort the active site. Multiple MD simulations of the hairpin ribozyme consistently result in a change in the A-1 sugar pucker in the absence of the 2′-O-methyl modification present in the experimental structure, leading to significant repositioning of the catalytically important nucleotides G8 and A38 (Figure 3B).…”
Section: What Are Specific Questions That MD Simulations Of Rna Can Cmentioning
confidence: 99%
“…Wildtype and all mutant structures (Table 1) were net-neutralized with sodium ions placed by the LEaP module at the points of greatest electrostatic favourability, resulting in an ion concentration of ~0.13–0.16 M. Despite the difference from typical experimental conditions (typically ~11–12 mM Mg 2+ , e.g., 19,21,33 ), we used neutralizing monovalents as we have in most of our previous work (e.g., 11,12,19,4244 ). Our rationale for this protocol has been previously summarized 43,45 ; most prominently, force field parameters for sodium are very well-defined, unlike those for Mg 2+ , especially given the latter’s strong tendency to polarize the phosphate group, which is ill-described in current force fields.…”
Section: Computational Detailsmentioning
confidence: 99%
“…55 and in-line fitness components were calculated using the ptraj module in AMBER10/11. 47,48 Following the rationale in our previous work (e.g., 11,12,19,4244 ), we chose to conduct 4 replicates of each 20 ns for each of our mutants, instead of longer simulations, for two reasons: (1) In longer simulations, the later time points are dependent on the evolution of earlier time points, whereas in our smaller simulations, we are able to investigate greater phase space with multiple fresh simulations; and (2) Longer simulations are more vulnerable to force field artefacts.…”
Section: Computational Detailsmentioning
confidence: 99%